Multi-species fish pond and nutrient balance - Rahman, Mohammad Mustafizur; Verdegem, Marc C.J. (Wageningen Academic Publishers, 2007)
The efficiency of pond aquaculture largely depends on species combination, stocking density and ratio, and the quantity and quality of nutrient inputs. In semi-intensive polyculture, fish production is mainly based on natural productivity, which greatly depends on nutrients availability in the water column. Addition of benthivorous fish enhances the release of nutrients from the sediment, stimulating phytoplankton productivity and accelerating the flux of nutrients to higher trophic levels. Density of benthivorous fish is very important. Optimum density of benthivorous and planktivorous fish in polyculture can improve synergistic effects, which increase nutrient retention efficiency in fish and decrease nutrient loss. Besides decreasing nutrient loss this type of polyculture maximizes resource utilization. This type of aquaculture is very appropriate in Asia, where investments in waste treatment are minimal or non-existant.